The relationship between globular cluster parameters and abundance variations. Issue Volume 14:Issue S351(2019) (May 2019) - Nataf, David M.
Abstract: We discuss a meta-analysis of the association of abundance variations in globular cluster stars with the present-day stellar mass and metallicity of globular clusters. Using data for 42 globular clusters that are well-sampled from either or both of prior literature studies and the APOGEE survey, we confirm prior findings that increasing aluminum abundance variations in globular clusters are positively correlated with increasing present-day stellar mass or decreasing metallicity. We also demonstrate that the ratio of aluminum abundance variations to either nitrogen abundance variations or sodium abundance variations is itself positively correlated with decreasing metallicity and increasing stellar mass of globular clusters. This suggests that there were at least two non-supernovae chemical polluters that were active in the early universe.